The Effect of Salmon Food-Derived DOM and Glacial Melting on Activity and Diversity of Free-Living Bacterioplankton in Chilean Patagonian Fjords - Montero, Paulina; Gutiérrez, Marcelo H.; Daneri, Giovanni; Jacob, Bárbara (Frontiers in Microbiology, 2022)
Fjord ecosystems cycle and export significant amounts of carbon and appear to be extremely sensitive to climate change and anthropogenic perturbations. To identify patterns of microbial responses to ongoing natural and human-derived changes in the fjords of Chilean Patagonia, we examined the effect of organic enrichment associated with salmon aquaculture and freshening produced by glacial melting on bacterial production (BP), extracellular enzymatic activity (EEA), and community diversity of free-living bacterioplankton. We assayed the effects of salmon food-derived dissolved organic matter (SF-DOM) and meltwaters through microcosm experiments containing waters from Puyuhuapi Fjord and the proglacial fjords of the Southern Patagonia Icefield, respectively. Rates of BP and EEA were 2 times higher in the presence of SF-DOM than in controls, whereas the addition of autochthonous organic matter derived from diatoms (D-DOM) resulted in rates of BP and EEA similar to those measured in the controls. The addition of SF-DOM also reduced species richness and abundance of a significant fraction of the representative taxa of bacterioplankton of Puyuhuapi Fjord. In the proglacial fjords, bacterioplankton diversity was reduced in areas more heavily influenced by meltwaters and was accompanied by moderate positive changes in BP and EEA. Our findings strongly suggest that SF-DOM is highly reactive, promoting enhanced rates of microbial activity while could be influencing the diversity of bacterioplankton communities in Patagonian fjords with a strong salmon farming activity. These findings challenge the traditional view of phytoplankton production as the primary source of labile DOM that fuels heterotrophic activity in coastal ecosystems impacted by anthropogenic organic enrichment. Given the intensive local production of salmon, we analyse the significance of this emerging source of rich "allochthonous" organic substrates for autotrophic/heterotrophic balance, carbon exportation, and hypoxia in Patagonian fjords. The effect of human DOM enrichment can be enhanced in proglacial fjords, where progressive glacial melting exerts additional selective pressure on bacterioplankton diversity.